Isolation and characterization of CAC antenna proteins and photosystem I supercomplex from the cryptophytic alga Rhodomonas salina. Issue 1 (4th March 2019) - Kuthanová Trsková, Eliška; Bína, David; Santabarbara, Stefano; Sobotka, Roman; Kaňa, Radek; Belgio, Erica
Abstract : In the present paper, we report an improved method combining sucrose density gradient with ion‐exchange chromatography for the isolation of pure chlorophyll a/c antenna proteins from the model cryptophytic alga Rhodomonas salina . Antennas were used for in vitro quenching experiments in the absence of xanthophylls, showing that protein aggregation is a plausible mechanism behind non‐photochemical quenching in R. salina . From sucrose gradient, it was also possible to purify a functional photosystem I supercomplex, which was in turn characterized by steady‐state and time‐resolved fluorescence spectroscopy. R. salina photosystem I showed a remarkably fast photochemical trapping rate, similar to what recently reported for other red clade algae such as Chromera velia and Phaeodactylum tricornutum . The method reported therefore may also be suitable for other still partially unexplored algae, such as cryptophytes.